Safety and immunogenicity of PHH-1V booster against SARS-CoV-2 variants, including omicron subvariants: Results from a phase IIb open-label extension study - María Jesús López; Maria Del Mar Vazquez; Melchor Alvarez-Mon; José Ramón Arribas; Eunate Arana-Arri; Patricia Muñoz; Jorge Navarro-Pérez; Rafael Ramos; José Molto; Susana Otero-Romero; Elena Aurrecoechea; Roc Pomarol; et al. (Human Vaccines & Immunotherapeutics)
SARS-CoV-2 vaccination campaigns on current endemic situation would benefit from vaccine alternatives with easy logistics and accessibility, sustained response and cross-reactivity against emerging variants. Herein, safety and immunogenicity of PHH-1V, adjuvanted recombinant RBD-based vaccine, as fourth dose for the most prevalent SARS-CoV-2 variants in Spain in subjects ≥18 years was investigated for 6 months in HIPRA-HH-2 open-label extension study. Subjects received a fourth dose of PHH-1V after either two BNT162b2 doses plus one PHH-1V dose (cohort 1) or three BNT162b2 doses (cohort 2). As regulatory endpoint, neutralization titers were investigated for PHH-1 V as fourth dose vs BNT162b2 as third dose in subjects receiving previous BNT162b2-based regimens. PHH-1 V immunogenicity (GMT) was investigated against Beta, Delta, and Omicron BA.1, BA.4/5 and XBB.1.5 on Days 14, 98 and 182 post-immunization. Two hundred and eighty-eight subjects received PHH-1V. Neutralizing antibodies against Omicron BA.1 at Day 14 significantly increased after the PHH-1V as fourth booster vs the third BNT162b2 booster (GMT ratio 0.43 (95% CI: 0.28; 0.65; p-value < .0001)). PHH-1V fourth booster induced a significant increase in neutralizing titers vs baseline (GMFR on Day 14 [95% CI]: Beta 6.96 [5.23, 9.25]; Delta 6.27 [4.79, 8.22]; Omicron BA.1 9.21 [5.57, 15.21]; Omicron BA.4/5 11.80 [8.29, 16.80]; Omicron XBB.1.5 5.22 [3.97, 6.87]), remaining significantly higher up to 6 months. The most frequent adverse events were injection site pain and fatigue. As conclusion, PHH-1V booster induced sustained humoral and cellular immune response against Beta, Delta variants and cross reactivity against distant Omicron subvariants and could be an appropriate strategy for implementing heterologous vaccination campaigns.